The Concept of Amanah in Islamic Banking and Its Responsibilities: An Overview in Islamic Economic Philosophy - Didik Supardana Setia Aksana (Journal of Economic Perspectives and Business Innovation, 2024)
AbstractThe concept of amanah (trustworthiness) is a fundamental ethical principle in Islamic banking and serves as a cornerstone of Islamic economic philosophy. This study explores the meaning, dimensions, and practical implications of amanah in the responsibilities of Islamic financial institutions. Using a qualitative conceptual approach, the research reviews classical Islamic sources, contemporary banking practices, and ethical frameworks to understand how trust is institutionalized in financial transactions. The findings show that amanah extends beyond contractual compliance to include moral accountability, transparency, fairness, and protection of stakeholders’ interests. Islamic banks are expected to uphold trust by ensuring responsible fund management, risk-sharing principles, and adherence to Sharia values. The study concludes that strengthening the implementation of amanah is essential for maintaining public confidence, promoting ethical finance, and supporting sustainable economic development within the Islamic banking system. Keywords: amanah, Islamic banking, trust, Islamic economic philosophy, ethical finance